EFEKTIVITAS CELEBRITY ENDORSER TITAN TYRA TERHADAP SIKAP FOLLOWERS INSTAGRAM @TITANTYRA - Dimas Andriyanto (2021)
Celebrity endorsers are one of the digital marketing communication strategies that are currently being carried out due to the high number of social media users. Titan Tyra has become a celebrity endorser with a focus on beauty content, style of dress, and lifestyle with various products being promoted, this is evidenced by the number of products that are suitable or not with a focus on content through the @titantyra Instagram account. The approach used in the research is a quantitative survey that tests the TEARS Theory which stands for trustworthiness, expertise, attractiveness, respect, and similarity to 100 Instagram followers @titantyra. The sampling technique used was Nonprobability Sampling, while the data processing used a questionnaire. The effectiveness of celebrity endorsers in the digital marketing communication process is as a message through Instagram media and is measured based on the TEARS dimension according to Shimp while the attitude which is the effect and feedback of the digital marketing communication process is measured based on three (3) dimensions, namely cognitive, affective, and conative. The results of the Correlation Test show a significance value of 0.000 which indicates a correlation because it is located at <0.05. The calculated r coefficient is 0.618 which indicates a strong correlation. The results of a simple linear regression test show that the direction of the effectiveness of the celebrity endorser Titan Tyra on the attitude of Instagram followers @titantyra is positive. The results of the coefficient of determination show that there is an influence of 37.8% between the effectiveness of the celebrity endorser Titan Tyra on the attitude of Instagram followers @titantyra. These results are reinforced by the results of hypothesis testing which states that Ho is rejected and Ha is accepted, meaning that there is an influence between the effectiveness of celebrity endorsers on followers' attitudes. The conclusion of the study is that the effectiveness of celebrity endorser Titan Tyra affects the attitude of Instagram followers @titantyra.